“Modernas! São Paulo vista por elas”: the Jewish presence in the formation of Brazilian modernism in the light of Public History (Ágora Journal, 2024)
In this article we will discuss some aspects of the exhibition “Modern! São Paulo seen by them”, brought by the Jewish Museum of São Paulo, and the photographic narratives produced by 7 Jewish women who came to Brazil between the 1930s and 1950s. Restricted to contexts of production and dissemination, outside of ordinary circles, the works reveal a strong contribution to Brazilian modernism.What the museum proposes is the expansion of the public to a history unknown, but that can be thought from the contributions of Public History, while intertwining with the aesthetic experience of Walter Benjamin (1994).
Keywords: Judaism; Modernism; photography.